2002
DOI: 10.1046/j.1537-2995.2002.00145.x
|View full text |Cite
|
Sign up to set email alerts
|

Removal of neutralized model parvoviruses and enteroviruses in human IgG solutions by nanofiltration

Abstract: BACKGROUND: Nanofiltration has proven to be an effective technology for virus removal. The small nonenveloped viruses, such as HAV and parvovirus B19 (B19), are evidently more difficult to remove than the larger enveloped viruses. However, since antibodies against these viruses, HAV and B19, are constantly present in large plasma pools, it is conceivable that antibody binding will lead to an increase in size of the viruses due to a corona of antibodies on the virus surfaces. These enlarged viruses should be ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 16 publications
3
44
0
1
Order By: Relevance
“…This new 12% IgG solution differs from other IVIG products in various ways. Its virus safety is based on a series of pathogen inactivation and elimination steps, including nanofiltration, a technology that has the potential to enhance the prion-elimination capacity of the fractionation process as well [8][9][10]. Most importantly, however, the new formulation is stabilized by a novel approach being based on the excipients nicotinamide, L-proline, and L-isoleucine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This new 12% IgG solution differs from other IVIG products in various ways. Its virus safety is based on a series of pathogen inactivation and elimination steps, including nanofiltration, a technology that has the potential to enhance the prion-elimination capacity of the fractionation process as well [8][9][10]. Most importantly, however, the new formulation is stabilized by a novel approach being based on the excipients nicotinamide, L-proline, and L-isoleucine.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been shown that IgG preparations with a high dimer content were poorly tolerated [5][6][7]. Nanofiltration was introduced as an additional physical virus removal step, which also effectively contributes to the removal of the transmissible spongiform encephalopathy (TSE) agents in experimental models [8][9][10]. Furthermore, IVIG-F10 contains no sucrose or other carbohydrates and its immunoglobulin A (IgA) content is greatly reduced.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, small-pore nanofilters that assure removal of most small pathogens are not always compatible with high-volume products such as IVIG. Large-pore and small-pore nanofilters to remove viruses from IVIG have been evaluated [54]. The results demonstrated that large viruses, such as enveloped viruses and some antibody-complexed small nonenveloped viruses were effectively removed by an IVIG-compatible large-pore nanofilter.…”
Section: Ivigs and Pathogen Safety: Have We Eliminated All Risks In Nmentioning
confidence: 99%
“…PPV and other mammalian parvoviruses have been extensively used as models for virus reduction techniques. [37][38][39][40] Parvoviruses are one of the smallest known viruses (18-26 nm in diameter) 41 and are difficult to inactivate by chemical or heat treatment. 27 They are most effectively removed by 20 nm pore-size nanofilters, but these filters are known to foul easily and have high pressure drops.…”
Section: Virus Reduction By Htcc Blendsmentioning
confidence: 99%